A 17-Week Teacher-Implemented Story Writing Intervention With Year 2 Students in New Zealand: A Mixed Methods Study. Issue 4 (4th July 2021) - Finlayson, Kristen; McCrudden, Matthew T.
Abstract: We investigated the effectiveness and social validity of a 17-week teacher-implemented whole-class Self-Regulated Strategy Development (SRSD) story writing intervention with 6–7-year-old students in New Zealand. We used a mixed methods intervention design. In the quantitative strand, we conducted a quasi-experiment in which students either received SRSD writing instruction or their regular writing instruction. We collected student writing samples before and after the intervention and teachers completed a social validity questionnaire after the intervention. A mixed-model ANOVA with SRSD instruction as the between-subject variable and time as the within-subject variable indicated that students in the treatment group had higher quality stories (ES = 0.97), included more essential story writing components (ES = 1.61), and wrote longer stories (ES = 1.06), after the intervention than students in the comparison group. In the qualitative strand, we interviewed the classroom teachers to gain deeper understandings of their perceptions of the social validity of the intervention. They indicated that the intervention was appropriate to meet their goals, was beneficial for the students, and they enjoyed implementing the intervention. Thus, the intervention was effective and teachers perceived it to have social validity. Limitations and future directions are discussed.